READABILITY LEVEL OF âBAHASA INGGRISâ TEXTBOOK FOR THE SEVENTH GRADE STUDENTS - Fahriah, Fahriah; Rahayu, Puji Sri (LET: Linguistics, Literature and English Teaching Journal, 2015)
This research aims to investigateÂ the level of readability of âBahasa Inggrisâ textbook for Â the seventh grade students published by Mediatama Â and to know whether âBahasa Inggrisâ textbook is readable for the seventh grade students. The population of this study is +Â 210 students of seventh grade of SMP Negeri 1 Banjarmasin. The sample is 20% of the population or 42 students. TheÂ sample is chosen by using random-sampling techniquesÂ which is taken 6 students in each class.Â Â To collect the data, the writer uses two techniques that are cloze test and readability formula (Flesch Reading Ease Formula). Â The result of this research showedÂ that through Flesch Reading Ease Formula, the readability score for the whole texts of the English textbook entitled âBahasa Inggrisâ is 76,35 (fairly easy) and through cloze test, the textbook has high readability which shown by its readability score 62,068. It means that âBahasa Inggrisâ Textbook Published by medaiatama is readable and suitable for the seventh grade of SMP Negeri 1 Banjarmasin.